(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article provides a comprehensive analysis of Rizouddin Fakhriddin’s scientific heritage. The scholar’s religious-philosophical, historical-biographical, linguistic, and pedagogical ideas are examined in their interrelation, revealing his conceptual position based on the principle of “reform through enlightenment.” Fakhriddin’s ideas of Islamic renewal founded on ijtihad, his biographical methodology interpreting history through personalities, and his simplified approaches to language and education are evaluated as significant theoretical sources for modern Islamic and pedagogical studies. The article aims to contribute to the national direction of scientifically studying the country’s spiritual heritage.